New perspectives on targeted therapy in ovarian cancer - Coward JIG; Middleton K; Murphy F (Dove Medical Press, 2015)
Jermaine IG Coward,1–3 Kathryn Middleton,1 Felicity Murphy1 1Mater Health Services, Raymond Terrace, South Brisbane, QLD, Australia; 2Inflammtion and Cancer Therapeutics Group, Mater Research, University of Queensland, Translational Research Institute, Woolloongabba, Brisbane, QLD, Australia; 3School of Medicine, University of Queensland, Brisbane, QLD, Australia Abstract: Epithelial ovarian cancer remains the most lethal gynecologic malignancy. During the last 15 years, there has been only marginal improvement in 5 year overall survival. These daunting statistics are compounded by the fact that despite all subtypes exhibiting striking heterogeneity, their systemic management remains identical. Although changes to the scheduling and administration of chemotherapy have improved outcomes to a degree, a therapeutic ceiling is being reached with this approach, resulting in a number of trials investigating the efficacy of targeted therapies alongside standard treatment algorithms. Furthermore, there is an urge to develop subtype-specific studies in an attempt to improve outcomes, which currently remain poor. This review summarizes the key studies with antiangiogenic agents, poly(adenosine diphosphate [ADP]-ribose) inhibitors, and epidermal growth factor receptor/human epidermal growth factor receptor family targeting, in addition to folate receptor antagonists and insulin growth factor receptor inhibitors. The efficacy of treatment paradigms used in non-ovarian malignancies for type I tumors is also highlighted, in addition to recent advances in appropriate patient stratification for targeted therapies in epithelial ovarian cancer. Keywords: antiangiogenic therapy, high-grade serous, low grade ovarian cancer, PARP inhibition, cancer-related inflammation